2003
DOI: 10.1042/bj20021853
|View full text |Cite
|
Sign up to set email alerts
|

Gene disruption discloses role of selenoprotein P in selenium delivery to target tissues

Abstract: Selenoprotein P (SePP), the major selenoprotein in plasma, has been implicated in selenium transport, selenium detoxification or antioxidant defence. We generated SePP-knockout mice that were viable, but exhibited reduced growth and developed ataxia. Selenium content was elevated in liver, but low in plasma and other tissues, and selenoenzyme activities changed accordingly. Our data reveal that SePP plays a pivotal role in delivering hepatic selenium to target tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
355
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 390 publications
(375 citation statements)
references
References 31 publications
10
355
0
6
Order By: Relevance
“…During the systemic delivery of selenium, selenoprotein P that is present in the plasma is thought to be the selenium supply protein for the biosynthesis of the other selenoproteins including GPxs. 4,5 Recent evidence in selenoprotein P (SelP) knockout mice has shown that the distribution of selenium from the liver to testis and brain is mediated by Sel P. 6,7 It is also found that in the absence of SelP, selenium from selenious acid (SA, H 2 SeO 3 ) in the diet can be distributed to the peripherals by a yet unknown mechanism. 8 So far, little is known about the membrane transport of selenium from selenium source compounds, including SA.…”
Section: Introductionmentioning
confidence: 99%
“…During the systemic delivery of selenium, selenoprotein P that is present in the plasma is thought to be the selenium supply protein for the biosynthesis of the other selenoproteins including GPxs. 4,5 Recent evidence in selenoprotein P (SelP) knockout mice has shown that the distribution of selenium from the liver to testis and brain is mediated by Sel P. 6,7 It is also found that in the absence of SelP, selenium from selenious acid (SA, H 2 SeO 3 ) in the diet can be distributed to the peripherals by a yet unknown mechanism. 8 So far, little is known about the membrane transport of selenium from selenium source compounds, including SA.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we expected profound changes in the thyroid hormone axis, since all three types of iodothyronine-deiodinases (Dio) are selenoenzymes. Surprisingly, no disturbances of Dio activities were observed in liver, kidneys, or brains from our SePP-deficient mice despite decreased activities of other selenoenzymes (19). Even more surprising was the finding that in thyroid, not only Dio1, but also Gpx1 activity of SePP(7/7) mice was not reduced, although brain Gpx1 activity was decreased (Schomburg et al, in revision).…”
Section: Selenoprotein Pmentioning
confidence: 59%
“…Total serum Se concentrations were determined by the analytical method involving piazselenol formation and fluorimetric quantification as previously described (10,13). SePP concentrations were measured by the immunoluminometric sandwich assay established recently (9).…”
Section: Methodsmentioning
confidence: 99%
“…SePP concentrations were measured by the immunoluminometric sandwich assay established recently (9). GPx3 activity was determined by the coupled enzymatic assay with t-butylhydroperoxide as substrate (13).…”
Section: Methodsmentioning
confidence: 99%